2010
DOI: 10.1093/aobpla/plq006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salinity on water relations of wild barley plants differing in salt tolerance

Abstract: Root hydraulic conductivity was decreased by salinity in barley plants in parallel with slower transpiration rates and a down-regulation of aquaporin expression in the roots. The effects were larger and faster in a more salinity-tolerant line.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 39 publications
5
32
1
1
Order By: Relevance
“…Recent research has confirmed that stomatal closure at the beginning of salinity exposure can contribute to a decline in the flow of toxic ions within the transpiration stream [135][136][137]. Decreases in stomatal conductance due to salinity have been found in several different plant species [45,138].…”
Section: Effects Of Salinity On Leaf Water Relations and Gas Exchangementioning
confidence: 90%
See 2 more Smart Citations
“…Recent research has confirmed that stomatal closure at the beginning of salinity exposure can contribute to a decline in the flow of toxic ions within the transpiration stream [135][136][137]. Decreases in stomatal conductance due to salinity have been found in several different plant species [45,138].…”
Section: Effects Of Salinity On Leaf Water Relations and Gas Exchangementioning
confidence: 90%
“…Previous comparisons of water relations in some barley cultivars with different drought resistance levels showed that lower stomatal conductance and transpiration at the beginning of salt exposure contributed to higher salt tolerance in terms of improved extension growth and less accumulation of toxic ions [137]. Other authors have reported that stomatal responses to different abiotic stress are probably regulated by root signals, as occurs in drying and re-wetting soils [142,143].…”
Section: Effects Of Salinity On Leaf Water Relations and Gas Exchangementioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Fricke et al (2010) reported that water loss in salinized barley plants remained lower than normal conditions due to stomata closure under salt stress. Likewise, Vysotskaya et al (2010) reported that salt treatment (75 mM) inhibited water loss in tolerated barley cultivars more than sensitive cultivars.…”
Section: Growth Rate Water Loss and Root/shoot Ratio Of Triticale Gementioning
confidence: 97%
“…Relative water content (RWC) has been widely accepted as a reproducible and meaningful index of plant water status (Smart, 1974). It has been demonstrated that salt stress also affected and decreased RWC (Vysotskaya et al, 2010) but Sohail et al (2009) showed that increasing salt concentrations also led to a significant increase in relative water contents of leaf and root tissues.…”
Section: Introductionmentioning
confidence: 99%